The Reconstruction of Communal Property: Membership and Rights in Limpopo's Restitution Process - Espen Sjaastad; Bill Derman; Tshililo Manenzhe (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2011)
This paper analyses the problem membership in the Communal Property Associations that represent beneficiaries in the South African restitution of farmland. The recreation of a recipient communities raises important issues about the meaning of rights, the meaning of community, and the power to decide about these meanings. The paper shows how material considerations have influenced the choices of the actors involved, from prospective members to central government, in a cluster of rural restitution cases in Limpopo Province. In part, the primacy of material considerations reflects the success of the government in deflecting the focus of the land reform process away from justice and towards economic realities. These considerations have also served to exacerbate problems related to overlapping land claims, multiple membership, the ambiguous role of traditional leaders in land reform, gender discrimination, and – more generally – an uneven distribution of the benefits or land restitution. These problems have emerged in a context where government, under pressure to achieve a lot in a limited amount of time, failed properly to analyse and anticipate the scale and nature of the difficulties associated with communal land claims and the formal recreation of community. The result is a land restitution process that in its attempt to resolve old forms of injustice may end up producing new ones
Keywords: Q11; 330; Land restitution; South Africa; Limpopo; Communal Property Associations; membership